2019
DOI: 10.1108/raf-01-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the dimensions of CEO power and corporate social responsibility

Abstract: Purpose This study empirically aims to examine the relation between CEO power and firm engagement in corporate social responsibility (CSR). It undertakes an in-depth analysis of how the structural, ownership and expert dimensions of CEO power affect individual dimensions of CSR. Design/methodology/approach This study uses ordinary least squares and industry fixed-effects regressions. It also uses instrumental variable-generalized method of moment regressions to test the robustness of empirical results. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 55 publications
6
70
2
Order By: Relevance
“…These results seem to suggest that prior studies' (e.g., [9]) findings of the positive relationship between CEO ownership and CSR activities may be because most of the firms at the time were facing negative performance feedbacks. In contrast, the findings of prior studies (e.g., [10][11][12]) supporting the negative relationship may be due to underrepresentation of the firms that are performing below their aspirations. At the least, our study suggests the usefulness of considering the PFM in investigating the relationship between CEO ownership and CSR activities.…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…These results seem to suggest that prior studies' (e.g., [9]) findings of the positive relationship between CEO ownership and CSR activities may be because most of the firms at the time were facing negative performance feedbacks. In contrast, the findings of prior studies (e.g., [10][11][12]) supporting the negative relationship may be due to underrepresentation of the firms that are performing below their aspirations. At the least, our study suggests the usefulness of considering the PFM in investigating the relationship between CEO ownership and CSR activities.…”
Section: Discussioncontrasting
confidence: 64%
“…Prior studies on the effects of CEO ownership on CSR have found mixed results (e.g., [9][10][11][12][13]). For example, Johnson and Greening [9] argued that ownership empowers executives and enables them to allocate resources among diverse stakeholders in a way that ensures continued stakeholder support in the longer run and found a positive relationship between top management equity and CSR.…”
Section: Ceo Ownership and Csrmentioning
confidence: 98%
See 3 more Smart Citations